STEM-based 2D Shapes Learning Design in Parachuting Context to Support Student’s Flexibility Ability - Ambarwati, Belinda; Aisyah, Nyimas; Hapizah; Ismail, Norulhuda (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
This research aims to produce STEM-based 2D shapes learning trajectories in the context of parachuting to support students’ flexibility ability. The method chosen was design research type validation studies consisting of three stages: preparation for experiment, design experiment, and retrospective analysis conducted for two cycles. The research subjects were 7th grade junior high school students selected by purposive sampling. Data were collected through observation, written tests, and interviews, then analyzed qualitatively and presented in text narratives. The result of this study is a learning trajectory consisting of three activities, namely 1) making three square-shaped canopy designs with different sizes and the same suspension rope length, 2) making three square-shaped canopy designs with the same size and different suspension rope lengths, and 3) making three canopy designs in the form of different quadrilateral with the same canopy area and suspension rope length. The learning trajectory developed is able to support students' flexibility ability where in the learning process students are directed to realize the existence of alternative strategy choices or varied solutions, utilize various knowledge possessed, determine the most effective and efficient way or strategy, and believe in the truth of the answers used in solving problems.